The american duplicity vis-a-vis the colonial problem of the Maghreb during the second world war - B HAROUNI (Revue des Sciences Humaines, 2003)
This article attempts to show the American Government’s duplicity towards the North African colonial problem during the Second World war. This duplicity is to be examined in the approach of the American Government to  Vichy France colonial authorities and North African nationalists during the preparation of the invasion of North Africa and during the presence of the Anglo-American expeditionary forces in this area.